A low rcs compact circularly polarized dual band slot antenna loaded with SRR and CSRR for satellite applications - Verma, Hridesh Kumar (2022)
In this work, a low radar cross-section (RCS) dual-band with one band circularly polarised (CP) slot antenna consisting of an L-shaped metallic strip along with a combination of Split Ring Resonator (SRR) and complementary SRR (CSRR) is proposed. In the dual-band, one wideband operation is obtained by creating a wide slot in the ground plane of the antenna and a narrow band is achieved by loading the antenna with a combination of SRR-CSRR. The proposed antenna achieves impedance bandwidth of 1.5 to 3.26 GHz and 3.6 to 4.1 GHz. The proposed design has 3-dB axial ratio bandwidth (ARBW) of 2.5 to 3 GHz and the peak gain of the antenna is 4.2 and 3.3 dBi in the respective bands. The proposed antenna exhibits significant RCS reduction in the wideband of 4.7 to 18 GHz and peak RCS reduction of 26 dB is achieved at 11.3 GHz. Also, the sense of polarisation of the proposed antenna can be changed by 90° rotating the L-shaped metallic strip with reference to the slot in the ground plane.